2009
DOI: 10.1002/mus.21343
|View full text |Cite
|
Sign up to set email alerts
|

Assay of diffusion of different botulinum neurotoxin type a formulations injected in the mouse leg

Abstract: Botulinum neurotoxin type-A (BoNT/A) is very effective in the therapy of a wide range of human syndromes characterized by hyperactivity of peripheral cholinergic nerve terminals. Little diffusion of this toxin from the site of injection is commonly observed, but even minor changes in this property would greatly affect the validity of the treatment. Different pharmacological formulations of BoNT/A are available, and they may have different diffusion characteristics due to protein complex size, product format, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 26 publications
3
58
0
2
Order By: Relevance
“…[24][25][26] Carli et al 24 showed no significant difference among ABO, ONA, and incobotulinumtoxinA injections in the FME of BoNTA in adjacent muscles. The effects of BoNTA in adjacent muscles depend on clinical, temporal, and EMG factors 26 and on physical aspects such as injection technique and muscle targeting.…”
Section: Discussionmentioning
confidence: 96%
“…[24][25][26] Carli et al 24 showed no significant difference among ABO, ONA, and incobotulinumtoxinA injections in the FME of BoNTA in adjacent muscles. The effects of BoNTA in adjacent muscles depend on clinical, temporal, and EMG factors 26 and on physical aspects such as injection technique and muscle targeting.…”
Section: Discussionmentioning
confidence: 96%
“…Peripheral spread away from the site of toxin injection is not dependent on auxiliary proteins (Brodsky et al, 2012;Carli et al, 2009). BoNT/A traffic from periphery to the CNS via axonal route is discussed in Section 6.…”
Section: Experimental Assessment Of Systemic Pharmacokinetic Of Intramentioning
confidence: 99%
“…Moreover, investigations on local injections of botulinum complex for a therapeutic purpose have confirmed that BoNT/A dissociates virtually immediately from ANTPs under physiological conditions [45,135]. Moreover, although BoNT remains relatively localized at the site of injection by binding to the local nerve endings, side effects of BoNT therapy have been observed due to toxin diffusion [26]. Most often, the undesired effects are related to local toxin diffusion to the adjacent muscles, but in rare cases, adverse effects occur in distant muscles or result in central effects or generalized intoxication [1,63,66,67,87,146,185].…”
Section: Bont Disseminationmentioning
confidence: 96%